2021
DOI: 10.2147/oajc.s301551
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Rights Knowledge, Health Care Utilization, and Contraceptive Use in Pakistan: A Reproductive Rights Perspective

Abstract: Introduction This study investigates the effects of utilization of health care and the level of reproductive rights knowledge on contraceptive use. Current family planning programs in developing countries utilize a two-pronged strategy involving improvement of level of reproductive rights and, right to access health care systems. The effectiveness of this strategy in developing countries such as Pakistan remains poorly investigated. This study aimed at examining the effect of reproductive rights k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…7 A study conducted in Peshawar showed that only 30.7% had correct information about contraception while 51% did not agree to practice it. 8 another study showed that condoms were mostly (65.5%) used as contraceptive .9 Mix reports are available one shows that education has no effect on contraception usage 10 On the other hand some reports show relationship 11 This research aims to identify the primary factors that drive such barriers by exploring the root causes of limited access and use of contraception among women. It also aims to understand why some women avoid it.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study conducted in Peshawar showed that only 30.7% had correct information about contraception while 51% did not agree to practice it. 8 another study showed that condoms were mostly (65.5%) used as contraceptive .9 Mix reports are available one shows that education has no effect on contraception usage 10 On the other hand some reports show relationship 11 This research aims to identify the primary factors that drive such barriers by exploring the root causes of limited access and use of contraception among women. It also aims to understand why some women avoid it.…”
Section: Introductionmentioning
confidence: 99%